Estratégia de marcas no varejo de alimentos: concepção e gestão de marcas próprias na Inglaterra e no Brasil - Paula, Verônica Angélica Freitas de (2008)
In the current competitive and dynamic environment, with constant changes concerning consumers' preferences, competitors' actions and also political and economical changes in different countries, marketing strategies are even more relevant as the market has reached a more significant role in the definition of the tendencies and the success or failure of companies. Among the marketing strategies, in this paper, branding strategies deserve more attention as they are also responsible to assure the company sustainable competitive advantage. Considering the retail sector, the brand is also one of the most important concepts in the marketing strategy, mainly because consumers usually make different analysis about the products from their brands, especially about image perception, price, value and quality. The identity of the brand's owner has a significant impact over the impressions consumers may have about this brand. Therefore, the decision about brands patronage is very important for retailers including the choice between offering national brands (that belong to manufacturers) and/or private labels (that belong to the retailers). The focus on this thesis concerns the study of private labels strategy in food retailers in England and in Brazil. In order to achieve the objectives of this study, a qualitative approach and the case study procedure have been used. As the empirical research was developed with different retailers and suppliers in England and in Brazil, the research strategy used was multiple cases study, as multiple experiments (with replication logic). For the interviews, semi-structured scripts were used. The results from the empirical research were presented individually by company and then by country. The results from both countries were analysed in a comparative way. From the comparative analysis, it was possible to identify the distinct characteristics of each country, as well as the factors responsible for the differences in retail and private labels. After the comparative analysis, it was possible to elaborate recommendations to help and guide retailers that are analysing the possibility to adopt private label strategies. A model was developed to summarize the main elements to be considered by food retailers during the decision of adopting private labels. Finally, limitations of the research and suggestions for further researches were presented.